Facial Palsy‐Specific Quality of Life in 920 Patients: Correlation With Clinician‐Graded Severity and Predicting Factors. (12th September 2018) - Tavares‐Brito, Joana; van Veen, Martinus M.; Dusseldorp, Joseph R.; Bahmad, Fayez; Hadlock, Tessa A.
Abstract : Objectives: To investigate the correlation between facial palsy severity and quality of life in a broad cohort of facial palsy patients and to elucidate factors that influence this relationship. Study Design: Retrospective study. Methods: Records of patients presenting with a clinician‐graded facial function (eFACE) and facial palsy‐specific quality‐of‐life patient‐reported outcome measure (FaCE) scale from the same moment were reviewed. Multiple linear regression was performed to study the effect of various variables on FaCE total score. Results: A total of 920 of 1, 304 patients were included, 59.9% female with a mean (standard deviation) age of 48.6 (16.7) years and a median (interquartile range palsy duration of 9.6 [2.2; 42.2] months. A multiple linear regression model predicting FaCE total score was established, finding 10 significant variables: eFACE; viral, malignant, and congenital etiologies; overweight status; anxiety; chronic pain; previous treatment; radiotherapy; and duration of palsy (R 2 = 0.261, P < 0.001). Gender, age, laterality, surgical etiology, depression, and timing of evaluation (at initial intake or at follow up) were not found to predict FaCE total scores. Conclusion: A correlation between facial palsy severity and quality of life was found in a large cohort of patients comprising various etiologies. Additionally, novel factors that predict quality of life in facial palsy were revealed. This information may help specialists to predict which facial palsy patients are at higher risk of a poorer quality of life, regardless of severity. Level of Evidence: 4 Laryngoscope, 129:100–104, 2019